PENGARUH PENGGUNAAN MEDIA KARTU BILANGAN TERHADAP KEMAMPUAN BERHITUNG PADA MATERI PENJUMLAHAN SISWA KELAS II SD INPRES BONTOALA I - Ramadhani, Rezky; Syam, Haerul; Sirajuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low arithmetic skills of second-grade students at Inpres Bontoala I in the area of addition, which were attributed to conventional teaching methods and a lack of concrete learning materials. This study aims to determine the effect of using number cards on students’ arithmetic skills. The method used was quantitative research with a quasi-experimental approach employing a nonequivalent control group design. The research sample consisted of two classes, namely the experimental class and the control class, selected using purposive sampling. Tests (pretest and posttest), observations, and documentation were used to collect data, which was then analyzed using descriptive and inferential statistics. The results showed an improvement in calculation skills in the experimental class, with a posttest average of 74.31 compared to 69.19 in the comparison class. Additionally, student learning activities in the experimental class fell into the active category. Meanwhile, the calculated t-value of 2.036 at a significance level of 0.05 yielded a calculated t-value > table t-value, specifically 2.036 > 1.99897. Therefore, it can be concluded that H0 is rejected and H1 is accepted. This means there is a significant effect of the use of number card media on arithmetic skills in the addition material for second-grade students at SD Inpres Bontoala I.